Analysis of Corporate Policy, Size, Profitability, Growth, and Ownership on The Corporate Value of Indonesian Banking Corporations - Kepramareni, Putu; Pradnyawati, Sagung Oka; Suryaningsih, Ni Wayan Ayu (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Stock prices are one of the attractions for investors when making investment decisions in the capital market. Corporates with good corporate value will also have good stock prices. In 2019 to 2021, data showed a significant deflation in banking sector stock prices, this deflation can be a negative assumption that affects the corporate value of the business entity. The author uses various factors both in terms of policy, namely dividend policy, firm size, profitability financial ratio, asset growth, and the influence of institutional ownership of the corporate. Data was obtained through the publication of issuer financial reports on the capital market. Data tabulation was tested using multiple linear regression. Testing shows that financial ratio analysis using profitability has a positive impact on corporate value, other tests involving dividend policy, firm size, entity asset growth and institutional share ownership did not show any significance on the value of the banking corporate being tested.